Insects - Ratnawati, Hazali; Siti Nurlydia, Sazali; Wan Nurainie, Wan Ismail; Marcellinus Isaac Stia, Dominic; Anis Norsyahira, Mohd Raffi; Fadzrahni Tarsha, Mohd Ustar; Mohd Ashraf, Abdul Mutalib; Nur Siti Aisyah, Zarimin; Qumiddin, Ab Razak; Siti Hanisah, Zahuri; Wahap, Marni; Mohamad Jalani, Mortada (UNIMAS Publisher and Wilmar Plantations Sdn Bhd, 2023)
Cosmodela aurulenta (Coleoptera: Carabidae), or commonly known as the golden-spotted tiger beetle, is a species commonly found in open areas or in lowlands near riverbanks. The species is 14 to 16 mm in length, the body is dark greenish with three distinctive spots on each sides of the elytra. There is also the presence of pale coloured hairs on the abdomen and legs. The species are known to be opportunistic predators of smaller invertebrates, with characteristic large mandibles and enlarged compound eyes. The species is also observed to show brief flights.